Conceptual design study on Plutonium-238 production in a multi-purpose high flux reactor - Jian Li; Jing Zhao; Zhihong Liu; Ding She; Heng Xie; Lei Shi (Nuclear Engineering and Technology, 2024)
Plutonium-238 has always been considered as the one of the promising radioisotopes for space nuclear power supply, which has long half-life, low radiation protection level, high power density, and stable fuel form at high temperatures. The industrial-scale production of 238Pu mainly depends on irradiating solid 237NpO2 target in high flux reactors, however the production process faces problems such as large fission loss and high requirements for product quality control. In this paper, a conceptual design study of producing 238Pu in a multi-purpose high flux reactor was evaluated and analyzed, which includes a sensitivity analysis on 238Pu production and a further study on the irradiation scheme. It demonstrated that the target structure and its location in the reactor, as well as the operation scheme has an impact on 238Pu amount and product quality. Furthermore, the production efficiency could be improved by optimizing target material concentration, target locations in the core and reflector. This work provides technical support for irradiation production of 238Pu in high flux reactors.